Expression of proteasome subunit isoforms during spermatogenesis in Drosophila melanogaster. - Ma, J.; Katz, E.; Belote, J.M. (Insect Molecular Biology, 2002)
In this study, we sought to identify and characterize all the proteasome genes of Drosophila melanogaster. Earlier work led to the identification of two genes encoding alpha4-type 20S proteasome subunit isoforms that are expressed exclusively in the male germline. Here we extend these results and show that six of the 20S proteasome subunits, and four of the 19S regulatory cap subunits, have gene duplications encoding male-specific isoforms. More detailed analyses of two of these male-specific subunits (Prosalpha3T and Prosalpha6T), using GFP-tagged reporter transgenes, revealed that they are predominantly localized to the nucleus at later stages of spermatogenesis and are present there in mature, motile sperm. These results suggest a possible role of a 'spermatogenesis-specific' proteasome in sperm differentiation and/or function.